PELATIHAN PEMANFAATAN MEDIA SOSIAL SEBAGAI MEDIA PEMASARAN KERAJINAN SANTRI BAITUL QUR'AN (Jurnal PkM Pemberdayaan Masyarakat, 2022)
Promotion through social media is nothing new. The benefits of social media on this one have been carried out for a long time, to apply the benefits of social media as a place to promote business because the number of internet users is now expanding. Some things that can be done as promotions on social media include product introductions, providing information to potential customers, and also reporting on ongoing promotions. For example, by providing information on product usage and discounts that are being given. By means of promotion that is easier and cheaper, the products offered can be promoted with a wider range without worrying about limitations such as distance, time, and funds used. One of the benefits of social media for business development is that it provides the ability to see market tastes. Through the habits that customers do on social media, it can be seen how their tastes change over time. In fact, customer or public responses to something new can also be seen. This of course can provide benefits for business people. Because, by doing so, business actors will gain knowledge about what products customers will like and how to promote them.